Magnetic properties of smart textile fabrics through a coating method with NdFeB flake-like microparticles. (July 2019) - Zhou, Yan; Zhu, Wei; Zhang, Lifang; Gong, Jingyu; Zhao, Dandan; Liu, Min; Lin, Long; Meng, Qi; Thompson, Richard; Sun, Ying
Coatings were prepared by using NdFeB flake-like microparticles with aqueous polyurethane polyol dispersions and were coated onto the surface of textile fabrics in order to obtain textile fabrics with good magnetic properties. X-ray diffraction and energy dispersive spectroscopy analysis showed that there was no significant oxidation and magnetic decline in the samples after 6 months. The surface morphologies of the textiles were characterized using scanning electron microscopy and optical microscopy. The results showed that the crack density (the number of cracks per unit area) increased with increasing magnetic microparticle content, which can be attributed to two reasons: on one hand, the stress concentration at areas of high powder concentrations fractured more easily; on the other hand, the expansion coefficients of magnetic microparticles and polymer materials are different. Three kinds of textile fabrics with different microparticle concentrations were magnetized by means of a magnetizing machine. It was found that the cotton knitted fabrics had the highest average surface magnetic induction intensity, reaching 19 mT when the content of magnetic microparticle was 50 wt%. It was considered that this was related to the magnetic field distribution, due to the surface friction coefficient of the textile fabrics and the positions/angles of the flake-like microparticles. The hysteresis loops were measured using a vibrating sample magnetometer, and the results showed that the higher the concentration of magnetic microparticles, the higher the magnetization of the fabric. In short, this method can be used to prepare fabrics with high magnetization required under special conditions.